Educational psychology : a realistic approach - Good, Thomas L.; Brophy, Jere E. (New York : Holt, Rinehart and Winston, 1977)
This interactive edition includes video and audio clips, activities and web-links. New to the seventh edition is a chapter on learning and instruction and updated information on topics such as: applying knowledge, Vygotsky's theory, self-efficacy, youth, self-esteem, creativity and bilingualism.
Includes index and references.
Keywords: Educational psychology; Psychology, Educational